Nurturing networks: Connecting the dots between social capital and antenatal care in south Karnataka, India - Avita R. Johnson; Sakthi Arasu; S Rathnakumari; William T. Story (Journal of Family Medicine and Primary Care)
Introduction: Antenatal care (ANC) is one of the pillars of primary healthcare in India. Timely and appropriate ANC can reduce complications from pregnancy and childbirth. Social capital—the collective benefit for an individual when part of a larger society—has the potential to improve the uptake of ANC services. Objective: To assess social capital and its association with ANC utilization in a peri-urban area in south India. Methodology: A cross-sectional study was conducted in two sub-center areas of Anekal Taluk in Bangalore Urban District, south India. A total of 350 women were interviewed on socio-demography, obstetric history, ANC utilization, and social capital. A composite index for quality ANC was constructed from various ANC services and social capital was measured using a validated 13-item instrument. Bivariate associations with socio-demographic variables, obstetric factors, and social capital were assessed. Logistic regression models were used to determine the association between quality ANC and social capital after controlling for covariates. Results: Mean age was 24.19 ± 3.56 years and mean education was 9.03 ± 4.98 years. Of all the women, 85% were homemakers and 70% belonged to the lower and middle classes. Quality ANC was achieved by 42.8% of the women. Being from Handenahalli subcentre (OR: 2.21; 95% CI: 1.36–3.60), completing secondary (OR: 4.56; 95% CI: 1.86–11.17) or higher education (OR: 5.95; 95% CI: 2.28–15.51), being gainfully employed (OR: 2.18; 95% CI: 1.06–4.48), belonging to middle class (OR: 2.37; 95% CI: 1.24–4.53), and feeling like one belongs to the village (OR: 8.33; 95% CI: 1.73–40.11.53) were significant predictors of achieving quality ANC. Conclusion: Even though individual services of the ANC were achieved by more than 80% of women, quality ANC was accomplished by less than half. Apart from factors like education, occupation, and geographic area; social capital factors, like social cohesion, proved to be a strong predictor of quality ANC. Social capital should be leveraged to empower society to further strengthen access to quality ANC services.